2021
DOI: 10.4314/jasem.v25i9.10
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic extract of Ocimum Gratissimum (Scent Leaf) leaves improves haematological parameters in restrain-stressed rats

Abstract: Stress alters system physiology as well as humoral immunity and hematology, and its problems have become a global issue. The present study was designed to investigate effects of the use of traditional herbs such as Ocimum gratissimum (OG) on hematological parameters in stressed rats. We subjected adult female Wistar rats to prolonged restrained stress for 14 days and administered 100 mg/kg, 200 mg/kg, 400 mg/kg of OG leaf extract and Vitamin C respectively for 14 days. Animals (200-250 g) were sacrificed by ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…These medicinal potentials of OG are linked to its phytochemical constituents. Previously, we demonstrated that the OG attenuated chronic oxidative damage induced by LA on the spleen, thymus, and blood by reducing MDA levels and increasing antioxidant status [19] and mitigated restrained stress in rat models [20].…”
Section: Groups Dosagementioning
confidence: 87%
See 1 more Smart Citation
“…These medicinal potentials of OG are linked to its phytochemical constituents. Previously, we demonstrated that the OG attenuated chronic oxidative damage induced by LA on the spleen, thymus, and blood by reducing MDA levels and increasing antioxidant status [19] and mitigated restrained stress in rat models [20].…”
Section: Groups Dosagementioning
confidence: 87%
“…These intracellular enzymes (SOD and CAT), alongside non-enzymatic antioxidants (GSH), act as a primary defence line against the harmful effects of reactive oxygen species that may contribute to neurodegeneration in the brain. LA is regarded as a neurotoxin that induces oxidative damage and neurodegeneration via enhancing lipid peroxidation and the depletion of antioxidant status in the brain and other vital organs [19,20].…”
Section: Discussionmentioning
confidence: 99%